Toad poisoning in three dogs: case reports - Barbosa, C. M.; Medeiros, M. S.; Costa, Ciniro [UNESP]; Camplesi, A. C.; Sakate, M. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2009)
Toad poisoning is frequent in dogs, but has been infrequently addressed in published case reports and review articles. Dogs can be poisoned when they bite a toad or otherwise ingest the venom. The venom effects manifest soon after the accident, since the toxin is rapidly absorbed by the mucous membrane of the digestive system. Hospital records of three dogs, diagnosed with toad poisoning, were retrospectively reviewed from January 2005 to July 2007. Poisoned dogs may present only local irritation or systemic signs in the gastrointestinal, cardiac and neurological systems. All three cases presented herein had clinical signs of gastrointestinal alterations including vomiting, sialorrhea and diarrhea. Two dogs developed abnormal cardiac rhythm and two exhibited neurological signs. A poisoned animal requires emergency care and symptomatic therapy with intense monitoring of its clinical parameters. Although there have been reports on the low mortality of dogs poisoned by toads, one animal died even after appropriate therapy. The severity of clinical signs and the risk of death must be considered by the veterinarian.
Keywords: veterinary emergency; poisoning; toad venom; bufotoxin; Bufo sp.; dog